Social Media as an Informal Learning Environment: Opportunities and Risks for Student Development - Maryanti Sawitry; Irene Rosalina; Vita Pujawanti Dhana; Harlina Harja; Nurul Huda (Yayasan Adra Karima Hubbi, 2025)
Background. Social media platforms have increasingly become informal learning environments where students engage in knowledge sharing, collaboration, and skill development outside formal educational settings. Purpose. This study aims to explore the opportunities and risks associated with social media as an informal learning environment, focusing on its influence on cognitive, social, and emotional development. Method. A mixed-methods research design was employed, combining surveys of 250 students with semi-structured interviews to capture qualitative insights into learning behaviors, engagement patterns, and perceived benefits and drawbacks of social media usage. Results. Findings indicate that students leverage social media for collaborative learning, problem-solving, and information seeking, enhancing critical thinking and communication skills. However, exposure to inaccurate content, online distractions, and social comparison negatively impacted focus, motivation, and emotional well-being. Conclusion. The study concludes that while social media can serve as a valuable informal learning environment, structured guidance, digital literacy education, and awareness of potential risks are essential for maximizing benefits and mitigating harms.